Deficiency of TDAG51 Protects Against Atherosclerosis by Modulating Apoptosis, Cholesterol Efflux, and Peroxiredoxin‐1 Expression. Issue 3 (17th May 2013) - Hossain, Gazi S.; Lynn, Edward G.; Maclean, Kenneth N.; Zhou, Ji; Dickhout, Jeffrey G.; Lhoták, Šárka; Trigatti, Bernardo; Capone, John; Rho, Jaerang; Tang, Damu; McCulloch, Christopher A.; Al‐Bondokji, Imtisal; et al.
Abstract : Background: Apoptosis caused by endoplasmic reticulum (ER) stress contributes to atherothrombosis, the underlying cause of cardiovascular disease (CVD). T‐cell death‐associated gene 51 ( TDAG51 ), a member of the pleckstrin homology‐like domain gene family, is induced by ER stress, causes apoptosis when overexpressed, and is present in lesion‐resident macrophages and endothelial cells. Methods and Results: To study the role of TDAG51 in atherosclerosis, male mice deficient in TDAG51 and apolipoprotein E ( TDAG51 −/− / ApoE −/− ) were generated and showed reduced atherosclerotic lesion growth (56±5% reduction at 40 weeks, relative to ApoE −/− controls, P <0.005) and necrosis (41±4% versus 63±8% lesion area in TDAG51 −/− /ApoE −/− and ApoE −/−, respectively; P <0.05) without changes in plasma levels of lipids, glucose, and inflammatory cytokines. TDAG51 deficiency caused several phenotypic changes in macrophages and endothelial cells that increase cytoprotection against oxidative and ER stress, enhance PPARγ‐dependent reverse cholesterol transport, and upregulate peroxiredoxin‐1 (Prdx‐1), an antioxidant enzyme with antiatherogenic properties (1.8±0.1‐fold increase in Prdx‐1 protein expression, relative to control macrophages; P <0.005). Two independent case–control studies found that a genetic variant in the human TDAG51 gene region (rs2367446) is associated with CVD (OR, 1.15; 95% CI, 1.07 to 1.24; P =0.0003). Conclusions: These findings provide evidence that TDAG51 affects specific cellular pathways known to reduce atherogenesis, suggesting that modulation of TDAG51 expression or its activity may have therapeutic benefit for the treatment of CVD.